The Performance of Iraqi EFL University Students in Using Noun Clauses in English : Error Analysis - Khudhayer, Muneer Ali (جامعة بابل, 2013)
شبه ألجمله الاسمية هي عبارة غير مستقلة تعمل عمل الاسم .وهي واحدة من التراكيب الأساسية في النحو الإنكليزي ومجالا ذا صعوبة للطلبة الجامعيين العراقيين متعلمي اللغة الإنكليزية لغة أجنبية . \ تهدف الدراسة الى استقصاء اداء الطلبة الجامعيين العراقيين متعلمي اللغة الإنكليزية لغة أجنبية في استخدام أشباه الجمل الاسمية شكلا و وظيفة ,والكشف عن مجالات الصعوبة في هذا المجال ثم اقتراح برنامج علاجي تعليمي لتجاوز هذه الصعوبات. \ افترضت الدراسة إن الطلبة الجامعيين العراقيين متعلمي اللغة الإنكليزية لغة أجنبية يواجهون صعوبة في استخدام أشباه الجمل الاسمية في اللغة الانكليزية. \ تبدأ الدراسة بالجانب النظري الذي يشتمل على التعاريف وتصنيف اشباه الجمل الاسمية من حيث الصيغة والوظيفة وفي الجانب التطبيقي اختيرت عشوائيا عينة تتالف من(60) طالب من المرحلة الثالثة لقسم اللغة الانكليزية/ كلية التربية للعلوم الأنسانية/ جامعة بابل لتطبيق الاختبار الذي يغطي الجانبين التمييزي والأنتاجي . \ اظهرت نتائج الاختبار بأن الطلبة الجامعيين العراقيين متعلمي اللغة الأنكليزية لغة اجنبية يواجهون صعوبة في استخدام اشباه الجمل الاسمية وهذا بدوره يؤكد صحة فرضية الدراسة.في ضوء هذه النتائج ,استخلصت مجموعة من الاستنتاجات و الاقتراحات التي تشكل برنامج علاجي لتجاوز هذه الصعوبات التي يواجها الطلبة في استخدام اشباه الجمل الاسمية في اللغة الانكليزية. A noun clause is a dependent clause that works like a noun. It is one of the essential constructions in English grammar and a problematic area for the Iraqi EFL university learners. \ The study aims at investigating the performance of Iraqi EFL university students in using noun clauses by form and function and finding out the area of difficulty in this regard and suggesting remedial work for the alleviation of these difficulties . \ It is hypothesized that Iraqi EFL learners encounter difficulty in using noun clauses in English. \ The study begins with the theoretical aspect encompassing definitions, forms, and functions of noun clauses in English. Then, the practical aspect represented in a diagnostic test applied to a random sample of (60) students taken from the third level in the Department of English ,College of Education for Human Sciences, University of Babylon to assess Iraqi their performance at both the recognition and production levels. \ The findings of the test show that Iraqi EFL university students face difficulty in using noun clauses which, in turn, verifies the hypothesis of the study. In the light of the results of the test ,some conclusions are drawn and a number of suggestions and remedial work are presented so that the learners can overcome the difficulty they encounter in using noun clauses in English.
Keywords: التعليم العراقى -- اللغة الإنيليزية -- التحصيل الدراسى -- النحو الإنكليزى -- شبه الجملة الأسمية